Cry1Ac toxin binding in the velvetbean caterpillar Anticarsia gemmatalis: study of midgut aminopeptidases N - Lanzaro, M. D.; Padilha, I.; Ramos, L. F. C.; Mendez, A. P. G.; Menezes, A.; Silva, Y. M.; Martins, M. R.; Junqueira, M.; Nogueira, F. C. S.; AnoBom, C. D.; Dias, G. M.; Gomes, F. M.; et al. (Frontiers in Physiology, 2024)
The velvetbean caterpillar Anticarsia gemmatalis is one of the main soybean defoliators in Brazil. Currently, the main biopesticide used to control insect pests worldwide is the bacteria Bacillus thuringiensis (Bt), which produces entomopathogenic Crystal toxins (Cry) that act in the midgut of susceptible insects, leading them to death. The mode of action of Cry toxins in the midgut involves binding to specific receptors present on the brush border of epithelial cells such as aminopeptidase N (APN), alkaline phosphatase (ALP), cadherin, and others. Mutations in these receptors, among other factors, may be involved in the development of resistance; identification of functional Cry receptors in the midgut of A. gemmatalis is crucial to develop effective strategies to overcome this possible scenario. This study’s goal is to characterize APNs of A. gemmatalis and identify a receptor for Cry1Ac in the midgut. The interaction of Bt spores with the midgut epithelium was observed in situ by immunohistochemistry and total aminopeptidase activity was estimated in brush border membrane vesicle (BBMV) samples, presenting higher activity in challenged individuals than in control ones. Ten APN sequences were found in a A. gemmatalis’ transcriptome and subjected to different in silico analysis, such as phylogenetic tree, multiple sequence alignment and identification of signal peptide, activity domains and GPI-anchor signal. BBMV proteins from 5th instar larvae were submitted to a ligand blotting using activated Cry1Ac toxin and a commercial anti-Cry polyclonal antibody; corresponding bands of proteins that showed binding to Cry toxin were excised from the SDS-PAGE gel and subjected to mass spectrometry analysis, which resulted in the identification of seven of those APNs. Quantitative PCR was realized to compare expression levels between individuals subjected to sublethal infection with Bt spores and control ones, presenting up- and downregulations upon Bt infection. From these results, we can infer that aminopeptidases N in A. gemmatalis could be involved in the mode of action of Cry toxins in its larval stage.